1998
DOI: 10.1073/pnas.95.21.12586
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of DNA polymerase β in cell results in a mutator phenotype and a decreased sensitivity to anticancer drugs

Abstract: DNA polymerase ␤ (pol ␤) is the most error prone of all known eukaryotic DNA polymerases tested in vitro. Here, we show that cells overexpressing pol ␤ cDNA have acquired a spontaneous mutator phenotype. By measuring the appearance of mutational events using three independent assays, we found that genetic instability increased in the cell lines that overexpressed pol ␤. In addition, these cells displayed a decreased sensitivity to cancer chemotherapeutic, bifunctional, DNA-damaging agents such as cisplatin, me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
154
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 179 publications
(160 citation statements)
references
References 17 publications
6
154
0
Order By: Relevance
“…For example, mutations in mismatch repair and nucleotide excision repair genes, as well as de®ciencies that disrupt cell cycle checkpoints have been shown to predispose carriers to cancer, presumably by increasing genomic instability (Cahill et al, 1998;Wind et al, 1995). We recently identi®ed a new category of genetic event, overexpression of Pol b, the most inaccurate of all the mammalian DNA polymerases, that increased the spontaneous mutation frequency in CHO cells, supporting the concept that cancer may involve a mutator phenotype by higher expression of an error-prone DNA polymerase (Canitrot et al, 1998). Higher expression of Pol b has been observed in many tumor cell lines (Scanlon et al, 1989), including colon and ovarian cells.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…For example, mutations in mismatch repair and nucleotide excision repair genes, as well as de®ciencies that disrupt cell cycle checkpoints have been shown to predispose carriers to cancer, presumably by increasing genomic instability (Cahill et al, 1998;Wind et al, 1995). We recently identi®ed a new category of genetic event, overexpression of Pol b, the most inaccurate of all the mammalian DNA polymerases, that increased the spontaneous mutation frequency in CHO cells, supporting the concept that cancer may involve a mutator phenotype by higher expression of an error-prone DNA polymerase (Canitrot et al, 1998). Higher expression of Pol b has been observed in many tumor cell lines (Scanlon et al, 1989), including colon and ovarian cells.…”
Section: Discussionmentioning
confidence: 71%
“…DNA polymerase b gene expression in BCR ± ABL transfected Ba/F3 cells A recent study from our laboratory demonstrated that transfection of CHO cells by a vector overexpressing the DNA Polymerase b (Pol b) resulted in a spontaneous mutator phenotype (Canitrot et al, 1998). Pol b, structurally the simplest of the ®ve known mammalian DNA polymerases, is believed to function primarily in the repair of damaged bases (Sobol et al, 1996).…”
Section: Spontaneous Mutation Frequencies In Bcr ± Abl Transfected Bamentioning
confidence: 99%
“…Enhanced replicative bypass has been observed in human tumor cell lines with a defective MMR system (Vaisman et al, 1998). Furthermore, enhanced expression and activity of DNA polymerase b was found to correlate with cisplatin resistance (Mamenta et al, 1994;Canitrot et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Many repair proteins, in fact, are endowed with DNA trimming or modifying activities. Examples include APE1 or the DNA polymerase b (Polb); overexpression of these proteins has already been shown to promote genomic instability, possibly due to the lack of coordination of their enzymatic activities (26); (ii) repair factors may exert more than one specific function that cannot be directly linked to their DNA repair activity. This situation is nicely exemplified by the APE1 protein, which nucleolar localization is necessary for cellular proliferation (see below), or by proteins, such as the Werner syndrome helicase (WRN), or the flap 626 ANTONIALI ET AL.…”
Section: Dynamics Of Dna Repair Proteins During Genotoxic Damage: Nucmentioning
confidence: 99%